Information Technology Resource Framework - Hasugian, Paska Marto (Login : Jurnal Teknologi Komputer, 2024)
This study is a literature review aimed at investigating and analyzing concepts and frameworks related to Information Technology Resource. Through a literature review approach, this research gathers, organizes, and analyzes previous studies conducted in this field. The main focus of this study is to gain an understanding of the roles, components, and characteristics of the Information Technology Resource framework, as well as its impact on company performance. The method used in this research involves searching and selecting relevant scientific articles, journals, and publications related to the topic. After a careful selection process, the literature studies that meet the inclusion criteria are analyzed in detail, and relevant essential information is extracted for further analysis. The results of this literature review present various frameworks within the domain of Information Technology Resource. These frameworks encompass crucial aspects such as managing information technology resources, integrating information technology into business strategies, measuring information technology performance, and developing information technology competencies within organizations. In this context, the research identifies key concepts, theoretical perspectives, and recent trends in the development of Information Technology Resource frameworks.